Adaptive Strategies of Staphylococcus Species Isolated from Clinical and Healthcare En-vironments: Biofilm Formation, Methicillin and Natural Products Resistant Ability - Asma E. Altaher; Naima F. Bashee; Mona A. Ebrahim; Ameena I. Ahmed; AlZahraa A. Abdullah; Aisha M. Kanna; A. Abdulghani , Omayma; M. Shahlol , Aisha (Libyan Journal of Science &Technology, 2026)
Background and Aim: Staphylococcus species, Gram-positive cocci, are implicated in both nosocomial and commensal infections, attributed to biofilm formation on medical device surfaces and contaminated areas, often aggravated by insufficient cleaning practices. This study investigates biofilm formation, methicillin resistance, and the impact of Arabic gum extraction on Staphylococcus species in healthcare settings, offering epidemiological insights for infection prevention and control strategies. Patients and Methods: Staphylococcus spp. Were isolated from healthcare workers and outpatients, involving samples from skin, nasal, urine, and hospital environment sources. The isolates were identified by standard phenotypic methods, including colony characteristics, Gram staining, catalase, and coagulase tests. Antibiotic susceptibility and biofilm formation tests were conducted, and data were analyzed using Excel and Minitab Info. Results: - The findings indicate that 29.7% of Staphylococcus spp. are coagulase-negative, while 70.29% are coagulase-positive. Biofilm formation varied among the isolates, with coagulase-positive strains showing stronger biofilm production than coagulase-negative strains. Methicillin resistance was observed in healthcare workers, outpatients, and hospital environments. However, aqueous Arabic Gum extract demonstrated no impact on resistant strains, and 43% revealed biofilm formation. Conclusion: Furthermore, the study reveals that Staphylococcus spp. isolates from hospital surfaces, urine, and nasal sources exhibit higher methicillin resistance, with coagulase-negative Staphylococcus displaying lower biofilm formation. The study utilized a consistent concentration of Arabic Gum, and its effect on resistant strains remains uncertain.